2001
DOI: 10.1016/s0893-133x(01)00254-8
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine, but not Haloperidol, Increases Brain Concentrations of Neuroactive Steroids in the Rat

Abstract: The extrapyramidal side effects of typical antipsychotics, which are induced to a markedly reduced extent by clozapine, have been linked to a dysfunction of central ␥ -aminobutyric acid (GABA)-mediated neurotransmission. The effects of clozapine on the brain concentrations of 3 ␣ -hydroxy-5 ␣ AP) and 3 ␣ , THDOC)Clozapine, the prototype of atypical antipsychotic drugs, exhibits the clinical efficacy of classical antipsychotics but lacks or induces to a greatly reduced extent most of the motor side effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
1
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 54 publications
6
70
1
6
Order By: Relevance
“…It is therefore possible that olanzapine-and clozapine-induced elevations in the anxiolytic neuroactive steroid allopregnanolone contribute to the anxiolytic-like effects of these compounds. The absence of haloperidol-induced effects on this neuroactive steroid is consistent with recent efforts by Barbaccia et al (2001). To our knowledge, this is the first report demonstrating that acute risperidone administration does not affect central allopregnanolone levels.…”
Section: Discussion Olanzapine and Clozapine Effects On Cerebral Cortsupporting
confidence: 90%
See 2 more Smart Citations
“…It is therefore possible that olanzapine-and clozapine-induced elevations in the anxiolytic neuroactive steroid allopregnanolone contribute to the anxiolytic-like effects of these compounds. The absence of haloperidol-induced effects on this neuroactive steroid is consistent with recent efforts by Barbaccia et al (2001). To our knowledge, this is the first report demonstrating that acute risperidone administration does not affect central allopregnanolone levels.…”
Section: Discussion Olanzapine and Clozapine Effects On Cerebral Cortsupporting
confidence: 90%
“…Allopregnanolone levels in the cerebral cortex following clozapine administration in these experiments are comparable to levels reported recently by Barbaccia et al (2001), utilizing 10.0 and 20.0 mg/kg dosing strategies. In contrast to olanzapine and clozapine, the antipsychotics risperidone and haloperidol had no significant effects on allopregnanolone levels in the cerebral cortex, confirming our initial hypothesis.…”
Section: Discussion Olanzapine and Clozapine Effects On Cerebral Cortsupporting
confidence: 88%
See 1 more Smart Citation
“…Several preclinical studies have shown that haloperidol failed to alter the brain concentrations of neurosteroids (Barbaccia et al, 2001;Nechmad et al, 2003), whereas clozapine administered for 8 days reduced the brain concentrations of DHEA and DHEAS (Nechmad et al, 2003).…”
Section: Commentmentioning
confidence: 99%
“…It has recently been demonstrated that both olanzapine and clozapine, but not risperidone and haloperidol, elevate brain cortical levels of the GABA A -positive neuroactive steroid allopregnanolone (ALLO), leading to a putative increase in GABAergic tone (Barbaccia et al, 2001;Marx et al, 2000Marx et al, , 2003. Neuroactive steroids including ALLO are synthesized de novo in the brain from cholesterol or from peripheral steroids in adrenal or gonads (Purdy et al, 1991 and are present in the CNS at concentrations that may modulate GABA A receptor function Robel and Baulieu, 1995;Bixo et al, 1997;Rupprecht and Holsboer, 1999).…”
Section: Introductionmentioning
confidence: 99%